Not quite sur what you are really asking, so I will answer what I think your question could be asking.
If you are asking "How to solve by substitution", then you do three main things: (1) you simply pick one equation, and then isolate one of the variables in that equation. So let's take the 1st equation you gave, and let's isolate the y by subtracting x from both sides of that equation. So instead of x + y = 70, you do this: ( x - x ) + y = 70 - x. We are left with y = 70 - x.
(2) Now since you have a new eauation saying what y = , we can take that thing that y = , which is 70 - x, and replace (substitute) the "y" in the second equation you gave, with the 70 - x, since they are equal. So when you do that , instead of x - y = 24, we now have x - ( 70 - x ) = 24.
(3) Solve this new equation, and we will find what x = . Once we know x, we can take that number, and replace that number into the y = 70 - x equation to find y. So x - ( 70 - x ) = 24 becomes x - 70 + x = 24, and then 2x - 70 = 24. Move the 70 to the other side of the equals and divide both sides by 2, and we see that (70 + 24) / 2 = 47. Take that 47, replace that into the x position in y 70 - x, and you get y = 70 - 47, or y = 23.
Check you work by plug-n-check, and you will see that you have your answer.
Now........ does this answer your question?